Intrusion of Ptolemaic Reality on Cultic Practices in Qoh 4:17 - Aron Pinker (Journal of Hebrew Scriptures, 2010)
A new interpretation is offered for Qoh 4:17 that highlights the Sitz im Leben of the Ptolemaic regime. Qoh 4:17, though couched in cultic terms and with a Temple setting, contains allusions to the Ptolemaic reality of spies and informers who helped the Ptolemaic administration exact heavy taxes. It is shown that this dual level (cultic and non-cultic) meaning persists in the unit Qoh 4:17-5:6.